Preforming coating brazing filler metal and preparation method and application thereof
By using preformed coated brazing materials in battery cell ear welding, the problems of high flux cost, solvent volatility and low production efficiency are solved, and higher welding quality and lower void rate are achieved, which is environmentally friendly and efficient.
Patent Information
- Application Number
- CN202411992942.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The prior art has problems in the welding of battery cell ears, high flux cost, large amount of VOC, low production efficiency and unstable hollow rate in the welding of battery cells.
A preformed coated solder is provided, including zinc-aluminum alloy as the solder, an active agent wrapped around the periphery of the solder and a self-crosslinked emulsion as the solder. Through a specific coating and baking process, a coated solder material can effectively fill the battery cell electrode structure, improve welding quality and reduce cavitation rate.
The preformed coated solder can effectively fill the battery cell pole hole structure, improve production yield, reduce welding void rate, reduce flux peeling and solvent volatility, and improve welding quality and environmental protection.
Smart Images

Figure BDA0005224017600000061 
Figure BDA0005224017600000071 
Figure BDA0005224017600000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of brazing, and in particular to a preformed coated brazing material and a preparation method and application thereof. Background Art
[0002] The application scenarios of square batteries are very wide. They are widely used in electric vehicles, wireless devices, industrial equipment and medical equipment. In new energy vehicles, aluminum shell square lithium batteries are very common. It has a simple structure and can be adjusted arbitrarily according to the application scenario, suitable for a variety of electronic devices.
[0003] The production cost of battery cells has been reduced to a certain extent through continuous process improvement. In the increasingly fierce competition, it is necessary to continuously reduce costs and increase efficiency to reduce various manufacturing costs. Generally, a mixture of flux and solvent is applied before induction welding, and welding is performed in a wet state. The cost of flux remains high and the solvent evaporates to produce a large amount of VOC. This patent develops a preformed coated solder suitable for battery cell tab welding and a preparation method thereof, which can be easily assembled and adapted to automation, and has the characteristics of no spatter and little residue, reducing labor and flux costs, and is relatively environmentally friendly, with high production efficiency, stable void rate and lower void rate.
[0004] In view of this, this application is filed. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a preformed coated solder and a preparation method and application thereof. The preformed coated solder can well fill the battery cell tab structure, improve production yield, improve welding quality, avoid solder flux shedding, and effectively reduce welding void rate.
[0006] To achieve the above-mentioned object, in a first aspect of the present application, the present application provides a preformed coated solder, comprising a solder and a flux wrapped around the solder, wherein the solder comprises a zinc-aluminum alloy, and the flux comprises an activator and a film-forming substance;
[0007] The active agent includes a fluoroaluminate;
[0008] The mass ratio of the zinc-aluminum alloy to the fluoroaluminate is 100:(4-12);
[0009] The film-forming substance includes a self-crosslinking emulsion, and the mass ratio of the self-crosslinking emulsion to the active agent is (0.3-1):100.
[0010] As an implementation scheme of the present application, the mass percentage of aluminum in the zinc-aluminum alloy is 5 to 22%.
[0011] As an embodiment of the present application, the self-crosslinking emulsion includes a self-crosslinking acrylic emulsion and a self-crosslinking polyurethane emulsion; the mass ratio of the self-crosslinking acrylic emulsion to the self-crosslinking polyurethane emulsion is (1.5-9):1.
[0012] As an embodiment of the present application, the glass transition temperature of the cross-linked acrylic emulsion is ≤30°C.
[0013] As an embodiment of the present application, the minimum film-forming temperature of the self-crosslinking polyurethane emulsion is ≤0°C.
[0014] In a second aspect of the present application, the present application provides a method for preparing a preformed coated solder, comprising the following steps:
[0015] (1) uniformly mixing the flux, the self-crosslinking emulsion and the solvent to obtain a mixed solution;
[0016] (2) The mixed liquid is evenly coated on the surface of the solder and baked to obtain a preformed coated solder.
[0017] As an embodiment of the present application, the solvent includes at least one of water, ethanol, n-propanol, propylene glycol, propylene glycol butyl ether, ethylene glycol butyl ether, propylene glycol methyl ether, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, and dipropylene glycol dimethyl ether; and / or
[0018] The mass ratio of the solvent to the active agent is (0.8-1.5):1.
[0019] As an embodiment of the present application, step (2) is specifically as follows: applying the mixed solution to the solder surface in batches, with the amount of each coating not exceeding 1% of the total mass of the mixed solution, and baking after each coating to obtain a preformed coated solder.
[0020] Each baking temperature is greater than or equal to 0.8 times the boiling point of the solvent and less than or equal to 1.2 times the boiling point of the solvent;
[0021] Each baking time is 5 to 120 seconds.
[0022] As an embodiment of the present application, step (2) is specifically as follows: coating the mixed solution on the solder surface in batches, with the coating amount each time not exceeding 1% of the total mass of the mixed solution, and baking is maintained during the coating process to obtain a preformed coated solder.
[0023] Each baking temperature is greater than or equal to 0.8 times the boiling point of the solvent and less than or equal to 1.2 times the boiling point of the solvent.
[0024] In a third aspect of the present application, the present application provides an application of the preformed coated solder in the sealing of a battery cell tab structure.
[0025] As an embodiment of the present application, the preformed coated solder is placed in the middle of the weld formed by the pole and the battery core. During the high-frequency induction welding process, after the solder is melted, the molten liquid flows to fill the weld.
[0026] In a fourth aspect of the present application, the present application provides a battery cell tab, comprising the preformed coated solder described above.
[0027] The beneficial effects of the present invention are: (1) the preformed coated solder described in the present invention can well fill the battery cell tab structure and improve the production yield, and the solder pre-wrapped on the outer surface is to improve production efficiency and yield. The addition of self-crosslinking emulsion as a film-forming material in the present invention can effectively improve welding quality, avoid solder falling off, and effectively reduce welding void rate.
[0028] (2) The present application creatively adds a self-crosslinking emulsion comprising a self-crosslinking acrylic emulsion and a self-crosslinking polyurethane emulsion. The self-crosslinking emulsion can effectively improve the film-forming performance and effectively reduce the decomposition and splashing of organic matter during welding. Therefore, after welding, there is no need to clean the weldment, welding equipment and fixtures. At the same time, the decomposition of organic matter and the amount of smoke during welding can be reduced, thereby improving safety and environmental protection. The self-crosslinking acrylic acid can easily connect with the hydroxyl group in the flux during the film-forming process to form a coating on the metal surface. The self-crosslinking polyurethane emulsion and the self-crosslinking acrylic emulsion work together to improve the adhesion of the flux to the metal and the welding performance, thereby effectively reducing the welding void rate. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0030] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0031] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0032] In the present application, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0033] Unless otherwise specified, the components, raw materials or instruments used in the embodiments and comparative examples of the present invention are all commercially available raw materials or instruments, and the components and raw materials used in each parallel experiment are all of the same kind.
[0034] The inventors of the present invention have found that the existing induction welding technology generally uses a mixture of flux and solvent to apply before induction welding, and welding is performed in a wet state. However, the volatilization of the solvent and the instability of the application amount will cause low production efficiency and unstable void rate.
[0035] Therefore, in order to solve the above technical problems, the embodiment of the present application provides a preformed coated solder, comprising a solder and a solder flux wrapped around the outer periphery of the solder, wherein the solder comprises a zinc-aluminum alloy, and the solder flux comprises an activator and a film-forming substance;
[0036] The active agent includes a fluoroaluminate;
[0037] The mass ratio of the zinc-aluminum alloy to the fluoroaluminate is 100:(4-12), for example, it can be 100:4, 100:5, 100:6, 100:8, 100:10, 100:12 or a range consisting of any two of them;
[0038] The film-forming substance includes a self-crosslinking emulsion, and the mass ratio of the self-crosslinking emulsion to the active agent is (0.3-1):100, for example, it can be 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.8:100, 1:100 or a range consisting of any two of them. By controlling the mass ratio of the self-crosslinking emulsion to the fluoroaluminate within this range, the coating firmness and welding performance can be improved, and powder loss during the coating process can be avoided, while the amount of welding smoke can be effectively reduced.
[0039] The preformed coated solder described in the present invention can well fill the battery cell tab structure and improve the production yield, and the solder pre-wrapped on the outer surface is to improve production efficiency and yield. The addition of self-cross-linking emulsion as a film-forming material in the present invention can effectively improve welding quality, avoid solder falling off, and effectively reduce welding void rate.
[0040] The flux containing the activator is wrapped around the solder. The activator mainly removes the oxide film on the solder surface and the oxide film on the welding interface. Too low a content of flux has limited removal ability, which will affect the welding quality and further affect the product yield. Too high a content of flux will not improve the welding quality, but will lead to increased costs. Currently, the cost price of cesium fluoroaluminate flux is high (about 1.8 yuan / g), which is particularly valued in the cost-sensitive new energy vehicle industry chain.
[0041] In one embodiment, the mass percentage of aluminum in the zinc-aluminum alloy is 5-22%, for example, it can be 5%, 8%, 10%, 12%, 15%, 16%, 18%, 20%, 22% or a range composed of any two thereof.
[0042] In one embodiment, the self-crosslinking emulsion includes a self-crosslinking acrylic emulsion and a self-crosslinking polyurethane emulsion; the mass ratio of the self-crosslinking acrylic emulsion and the self-crosslinking polyurethane emulsion is (1.5-9):1, for example, it can be 1.5:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or a range consisting of any two values therein. The present application creatively adds a self-crosslinking emulsion comprising a self-crosslinking acrylic emulsion and a self-crosslinking polyurethane emulsion. The self-crosslinking emulsion can effectively improve the film-forming performance and effectively reduce the decomposition and splashing of organic matter during welding. Therefore, after welding, there is no need to clean the weldment, welding equipment and fixtures, etc., and at the same time, it can reduce the decomposition of organic matter and the amount of smoke during welding, thereby improving safety and environmental protection. The self-crosslinking acrylic acid is easily connected to the hydroxyl group in the brazing agent during the film-forming process to form a coating coated on the metal surface. The self-crosslinking polyurethane emulsion and the self-crosslinking acrylic emulsion work together to improve the adhesion and welding performance of the flux to the metal and effectively reduce the welding void rate.
[0043] In one embodiment, the glass transition temperature of the cross-linked acrylic emulsion is ≤30°C.
[0044] In one embodiment, the glass transition temperature of the cross-linked acrylic emulsion is -40 to 30°C, for example, it can be -40°C, -35°C, -30°C, -25°C, -20°C, -15°C, -10°C, -5°C, 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C or a range consisting of any two of the values.
[0045] Wherein, the glass transition temperature of the self-crosslinking acrylic emulsion is measured with reference to GB / T 27816 standard.
[0046] In one embodiment, the minimum film-forming temperature of the self-crosslinking polyurethane emulsion is ≤ 0°C.
[0047] In one embodiment, the minimum film-forming temperature of the self-crosslinking polyurethane emulsion is -45°C to 0°C, for example, it can be -45°C, -40°C, -35°C, -30°C, -25°C, -20°C, -15°C, -10°C, -5°C, 0°C or a range consisting of any two of these values.
[0048] In one embodiment, the minimum film-forming temperature of the self-crosslinking polyurethane emulsion is tested with reference to GB / T9267-2008 standard.
[0049] In one embodiment, the fluoroaluminate comprises CsAlF4, Cs2AlF5, Cs3AlF6, KAlF4, K2AlF5, K3AlF6, K2AlF5·H2O, KCs2Al3F 12 , at least one of CsK2AlF6, KZnAlF6, K2ZnAlF7, KZn2AlF8, KZnAl2F9, CsZnAlF6, Cs2ZnAlF7, CsZn2AlF8, and CsZnAl2F9.
[0050] An embodiment of the present application provides a method for preparing a preformed coated solder, comprising the following steps:
[0051] (1) uniformly mixing the flux, the self-crosslinking emulsion and the solvent to obtain a mixed solution;
[0052] (2) The mixed liquid is evenly coated on the surface of the solder and baked to obtain a preformed coated solder.
[0053] In one embodiment, the solvent includes at least one of water, ethanol, n-propanol, propylene glycol, propylene glycol butyl ether, ethylene glycol butyl ether, propylene glycol methyl ether, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, and dipropylene glycol dimethyl ether; and / or
[0054] The mass ratio of the solvent to the active agent is (0.8-1.5):1, for example, it can be 0.8:1, 1:1, 1.2:1, 1.5:1 or a range consisting of any two values therein.
[0055] In one embodiment, step (2) is specifically as follows: coating the mixed solution on the solder surface in batches, with the coating amount each time not exceeding 1% of the total mass of the mixed solution, and baking after each coating to obtain a preformed coated solder.
[0056] Each baking temperature is greater than or equal to 0.8 times the boiling point of the solvent and less than or equal to 1.2 times the boiling point of the solvent;
[0057] Each baking time is 5 to 120 seconds.
[0058] In one embodiment, step (2) is specifically as follows: coating the mixed solution on the solder surface in batches, with the coating amount each time not exceeding 1% of the total mass of the mixed solution, and baking is maintained during the coating process to obtain a preformed coated solder.
[0059] Each baking temperature is greater than or equal to 0.8 times the boiling point of the solvent and less than or equal to 1.2 times the boiling point of the solvent.
[0060] The inventors of the present invention have found that baking after coating will not be conducive to the film-forming material coating the solder surface, the flux is easy to fall off, and it is difficult to fully remove the oxide film on the solder surface and the oxide film on the welding interface during the welding process, resulting in an increase in the welding void rate, an increase in the bad rate of the tab welding, and low production efficiency. By adopting the specific coating and baking process of the present invention, the welding quality can be effectively improved, the flux can be prevented from falling off, and the welding void rate can be effectively reduced.
[0061] The drying process evaluation method is as follows: after the drying process is completed, 5 preformed coated solders are randomly selected and placed in a flat weighing bottle with constant weight, the weighing bottle is recorded as m0, the total weight of the preformed coated solder and the weighing bottle before drying is recorded as m1, the preformed coated solders are not stacked, dried at 100℃~105℃ for 10 minutes, taken out, cooled in a dryer at room temperature for 5 minutes, weighed and recorded as the total weight before drying as m2, and the weight loss rate is (m2-m0) / (m1-m0). Repeat the measurement of 5 preformed coated solders from the same batch for 3 times, and the absolute difference in weight loss rate obtained under repeatability conditions shall not exceed 1%, and the drying process can be considered feasible.
[0062] One embodiment of the present application provides an application of the preformed coated solder in the sealing of a battery cell tab structure.
[0063] In one embodiment, the preformed coated solder is placed in the middle of the weld formed by the pole and the battery core. During the high-frequency induction welding process, after the solder is melted, the molten liquid flows to fill the weld.
[0064] One embodiment of the present application provides a battery cell tab, comprising the preformed coated solder described above.
[0065] The sources of raw materials in the embodiments and comparative examples are shown in Table 1.
[0066] Table 1
[0067]
[0068]
[0069] The following examples are provided to facilitate understanding of the present invention. These examples are not provided to limit the scope of the claims.
[0070] Example 1
[0071] A method for sealing a battery cell tab with a preformed coated solder comprises the following steps:
[0072] (1) preparing ethanol and water into a solvent with an azeotropic point of 80° C.;
[0073] Preparing a preformed coated solder: uniformly mixing cesium fluoroaluminate (CsAlF4), a self-crosslinking emulsion and a solvent to obtain a mixed solution;
[0074] Wherein, the mass ratio of the self-crosslinking emulsion to cesium fluoroaluminate is 0.5:100; the self-crosslinking emulsion comprises a self-crosslinking acrylic emulsion 1 and a self-crosslinking polyurethane emulsion 1 in a mass ratio of 9:1;
[0075] The mass ratio of the solvent to cesium fluoroaluminate is 1.5:1;
[0076] The mass ratio of cesium fluoroaluminate to ZnAL10 is 8:100.
[0077] The mixed liquid is evenly coated on the solder (ZnAL10) surface for several times, and the coating amount each time is 0.5% of the total mass of the solder. After each coating, it is baked in an oven at 80° C. for 30 seconds to obtain a preformed coated solder.
[0078] (2) The preformed coated solder (height of 0.4 mm) is placed in the middle of the weld formed by the pole and the battery core. During the high-frequency induction welding process, after the solder is melted, the molten liquid flows to fill the weld. The high-frequency induction welding parameters are automatic control of induction current heating, current of 75 A, and duration of 3 seconds.
[0079] Embodiments 2 to 5
[0080] The difference between Examples 2 to 5 and Example 1 is that the baking temperature is changed.
[0081] Embodiment 6-7
[0082] The difference between Examples 6 and 7 and Example 1 is that the type of solvent and the baking temperature are changed.
[0083] Examples 8-9, Comparative Examples 1-2
[0084] The difference between Examples 8 to 9 and Comparative Examples 1 to 2 and Example 1 is that the mass ratio or the type of cesium fluoroaluminate and ZnAL10 is changed.
[0085] Embodiments 10 to 11
[0086] The difference between Examples 10 and 11 and Example 1 is that the mass ratio of the solvent to CsAlF4 is changed.
[0087] Examples 12-13, Comparative Examples 3-4
[0088] The difference between Examples 12 to 13 and Comparative Examples 3 to 4 and Example 1 is that the mass ratio of the self-crosslinking emulsion to cesium fluoroaluminate is changed.
[0089] Embodiments 14 to 19
[0090] The difference between Examples 14 to 19 and Example 1 is that the mass ratio or type of the self-crosslinking emulsion is changed.
[0091] Embodiment 20
[0092] The difference between Example 20 and Example 1 is that the baking steps are different.
[0093] A method for sealing a battery cell tab with a preformed coated solder comprises the following steps:
[0094] (1) preparing ethanol and water into a solvent with an azeotropic point of 80° C.;
[0095] Preparing a preformed coated solder: uniformly mixing cesium fluoroaluminate (CsAlF4), a self-crosslinking emulsion and a solvent to obtain a mixed solution;
[0096] Wherein, the mass ratio of the self-crosslinking emulsion to cesium fluoroaluminate is 0.5:100; the self-crosslinking emulsion comprises a self-crosslinking acrylic emulsion 1 and a self-crosslinking polyurethane emulsion 1 in a mass ratio of 9:1;
[0097] The mass ratio of the solvent to cesium fluoroaluminate is 1.5:1;
[0098] The mass ratio of cesium fluoroaluminate to ZnAL10 is 8:100.
[0099] The mixed liquid is evenly coated on the solder (ZnAL10) surface for multiple times, and the coating amount each time is 0.02% of the total mass of the solder. The coating process is continuously baked and dried at 80°C for 2700 seconds to obtain a preformed coated solder.
[0100] (2) A preformed coated solder (height of 0.4 mm) is placed in the middle of the weld formed between the pole and the battery core. During the high-frequency induction welding process, after the solder melts, the molten liquid flows to fill the weld.
[0101] Table 2
[0102]
[0103]
[0104] Performance Testing
[0105] Void rate test method: The preformed coated solder in the embodiment is placed in the middle of the weld formed by the pole and the battery core, and a welded part is obtained after high-frequency induction welding. A SONOSCAN-D9600 ultrasonic scanner is used to perform non-destructive ultrasonic scanning to measure the void rate of the weld surface. The ultrasonic probe parameters are: SK075 / 050 75MHz probe.
[0106] Mean value of void ratio: The void ratios of multiple groups of samples in each embodiment are counted and the arithmetic square is calculated. The result is the mean value of void ratio of each embodiment.
[0107] Void rate variance: The acoustic scanning void rates of multiple groups of samples in each embodiment are counted, and the average of the sum of squares of the differences between the void rates of the samples and the mean void rates is calculated. The result is the void rate variance of each embodiment.
[0108] Table 3
[0109]
[0110]
[0111] It can be seen from Table 3 that the preformed coated solder of the present invention can effectively improve the welding quality, avoid the flux from falling off, effectively reduce the welding void rate, can well fill the battery cell tab structure, and has broad application prospects.
[0112] Comparing Examples 1 to 7, it can be seen that when the baking temperature is less than 0.8 times the boiling point of the solvent or the baking temperature is greater than 1.2 times the boiling point of the solvent, the mean and variance of the welding void rate both increase. The lower baking temperature causes the solvent to remain in the solder. During induction welding, the solvent vaporizes to form a cavity, which hinders the contact reaction between the solder and the solder and the welding interface, and ultimately leads to an increase in the void rate; the higher baking temperature causes the self-crosslinking reaction of the self-crosslinking film-forming substance in the solder to be incomplete, and the solder cannot be well coated on the solder surface, and there is a phenomenon of flakes falling off, which ultimately leads to an increase in the welding void rate and variance. This conclusion can be applied to different solvent systems in the examples.
[0113] By comparing Examples 1, 8-9 and Comparative Examples 1-2, it can be seen that too low a flux content will result in a limited ability of the flux to remove oxide films, that is, it affects the flux's removal of oxide films on the solder surface and the solder interface. Too high a flux content will not improve the welding quality, but will cause too much flux residue after welding, reduce welding reliability, and increase costs.
[0114] By comparing Examples 1, 12-13, and Comparative Examples 3-4, it can be seen that when the mass ratio of the film-forming substance self-crosslinking emulsion to the activator is greater than 1:100, the average void rate after welding under the coating process is similar to that of the comparative example. The film-forming substance does not have the ability to remove the oxide film, and more film-forming substances hinder the contact between the brazing agent and the brazing material, reducing the welding reliability.
[0115] It can be seen from the comparison of Examples 1 and 14 to 17 that by controlling the mass ratio of the self-crosslinking acrylic emulsion to the self-crosslinking polyurethane emulsion to (1.5 to 9):1, the welding quality is further improved, the flux is prevented from falling off, and the welding void rate is further reduced.
[0116] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A preformed coated brazing material, characterized in that: It comprises a brazing material and a brazing flux wrapped around the outer periphery of the brazing material, wherein the brazing material comprises a zinc-aluminum alloy, and the brazing flux comprises an activator and a film-forming substance; The active agent includes a fluoroaluminate; The mass ratio of the zinc-aluminum alloy to the fluoroaluminate is 100:(4-12); The film-forming substance includes a self-crosslinking emulsion, and the mass ratio of the self-crosslinking emulsion to the active agent is (0.3-1):
100.
2. The preform coated solder according to claim 1, characterized in that: The mass percentage of aluminum in the zinc-aluminum alloy is 5-22%.
3. The preform coated brazing filler metal according to claim 1, characterized in that: The self-crosslinking emulsion includes a self-crosslinking acrylic emulsion and a self-crosslinking polyurethane emulsion; the mass ratio of the self-crosslinking acrylic emulsion to the self-crosslinking polyurethane emulsion is (1.5-9):
1.
4. The preform coated solder according to claim 1, characterized in that: The glass transition temperature of the cross-linked acrylic emulsion is ≤30°C; and / or The minimum film-forming temperature of the self-crosslinking polyurethane emulsion is ≤0°C.
5. The method for preparing the preformed coated solder according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) uniformly mixing the flux, the self-crosslinking emulsion and the solvent to obtain a mixed solution; (2) The mixed liquid is evenly coated on the surface of the solder and baked to obtain a preformed coated solder.
6. The method for preparing the preformed coated solder according to claim 5, characterized in that: The solvent comprises at least one of water, ethanol, n-propanol, propylene glycol, propylene glycol butyl ether, ethylene glycol butyl ether, propylene glycol methyl ether, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether and dipropylene glycol dimethyl ether; and / or The mass ratio of the solvent to the active agent is (0.8-1.5):
1.
7. The method for preparing the preformed coated solder according to claim 5, characterized in that: Step (2) is specifically as follows: coating the mixed solution on the solder surface in batches, with the coating amount each time not exceeding 1% of the total mass of the mixed solution, and baking after each coating to obtain a preformed coated solder. Each baking temperature is greater than or equal to 0.8 times the boiling point of the solvent and less than or equal to 1.2 times the boiling point of the solvent; Each baking time is 5 to 120 seconds.
8. The method for preparing the preformed coated solder according to claim 5, characterized in that: Step (2) is specifically as follows: coating the mixed solution on the solder surface in batches, with the coating amount each time not exceeding 1% of the total mass of the mixed solution, and baking is maintained during the coating process to obtain a preformed coated solder. Each baking temperature is greater than or equal to 0.8 times the boiling point of the solvent and less than or equal to 1.2 times the boiling point of the solvent.
9. Use of the preformed coated solder according to any one of claims 1 to 5 in the sealing of the tab structure of a battery cell.
10. The use according to claim 9, characterized in that: The preformed coated solder is placed in the middle of the weld formed by the pole and the battery core. During the high-frequency induction welding process, after the solder is melted, the molten liquid flows to fill the weld.
11. A battery cell tab, characterized in that: The present invention comprises the preformed coated solder according to any one of claims 1 to 4.
Citation Information
Patent Citations
Pre-arranged coating for surface fusion-covering technology and application thereof
CN105670433A
Soldering flux which generates few concaves after welding and is used for pre-formed soldering lug
CN105921911A
Method for producing solder electrode, method for producing laminate, laminate and electronic component
CN106463425A
Lithium battery module busbar connection structure
CN106784563A
Soldering flux capable of reducing exhaust emission treatment
CN109128582A
Cited By
Low-residue soldering flux and preparation method and application thereof
CN121696597A
Low-residue flux and preparation method and application thereof
CN121696597B
Low-residue flux, and preparation method therefor and use thereof
WO2026060979A1